Tanggung Jawab Pt Telkom terhadap Pelanggan Indihome Fiber Terkait Gangguan Jaringan Internet Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen(Studi Kasus PT Telkom Denpasar Bali): PT Telkom's Responsibility to Indihome Fiber Customers Regarding Internet Network Disruptions in the Light of Law Number 8 of 1999 concerning Consumer Protection (Case Study of PT Telkom Denpasar Bali) - I Made Surya Dharma; Budiar; Abdul Rahman (Pendidikan Al-Gafari, 2026)
In Law Number 9 of 1999 concerning Consumer Protection, Article 4 regulates consumer rights and Article 7 regulates the obligations of business actors. However, the reality in the field is that PT Telkom Denpasar Bali has not fully fulfilled customer rights as regulated in Article 4 and the obligations regulated in Article 7 of Law Number 9 of 1999 concerning Consumer Protection. The purpose of this study is to determine PT Telkom's Responsibility towards Indihome Fiber Customers regarding Internet Network Disruptions reviewed from Law Number 8 of 1999 concerning Consumer Protection. The data sources for this study are library research, observation, and interviews. The analysis carried out is qualitative analysis. The results of this study can be concluded that PT Telkom's Responsibility towards Indihome Fiber Customers regarding Internet Network Disruptions reviewed from Law Number 8 of 1999 concerning Consumer Protection has not fulfilled its responsibility for errors and negligence caused by PT Telkom in the Denpasar Bali area itself and network supervision and maintenance have not been properly maintained, so that customers feel disadvantaged as Indhome Fiber users and the slow handling of PT Telkom in repairing the network.